Princess Ellie takes charge - Kimpton, Diana; Finlay, Lizzie (New York : Hyperion Paperbacks for Children, 2007)
Princess Ellie loves being in the royal stable more than she likes living in the palace, but when Meg, the palace groom, gets sick, Ellie learns that taking care of the ponies is more difficult than it looks.
First published as: Princess Ellie saves the day. United Kingdom : Usborne, 2006.
4.2
K-3
Keywords: Princesses -- Juvenile fiction; Ponies -- Juvenile fiction; Princesses -- Fiction; Ponies -- Fiction; Horses -- Fiction; Princesses -- Fiction; Ponies -- Fiction; Horses -- Fiction; Princesses -- Fiction; Ponies -- Fiction